2021
DOI: 10.1007/s12119-021-09841-w
|View full text |Cite
|
Sign up to set email alerts
|

Employees, Advisees, and Emerging Scholars: A Qualitative Analysis of Graduate Students' Roles and Experiences of Sexual Violence and Sexual Harassment on College Campuses

Abstract: Sexual violence and sexual harassment (SVSH) are pervasive across university campuses. SVSH research rarely focuses on graduate students, who occupy unique positions within university settings due to their multiple responsibilities (e.g., teaching, research, mentoring), including managing unequal power dynamics with mentors and advisors. As part of a larger qualitative study, we sought to better understand SVSH generally and, when applicable, experiences of SVSH among graduate students on three campuses. Our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…No analogous research has been conducted in the UK; however, the prevalence of self-reported sexual aggression is notably higher amongst our participants compared to non-university males in the community, where 7.3.% disclose a history of such behaviors (Krahé et al, 2014). This supports prior contentions (e.g., Bloom et al, 2021) that universities are a breeding ground for sexual aggression and emphasizes the critical need for better harm prevention initiatives on campuses, including more evidence-based psychological interventions for male students who are at risk of offending.…”
Section: Discussionsupporting
confidence: 84%
“…No analogous research has been conducted in the UK; however, the prevalence of self-reported sexual aggression is notably higher amongst our participants compared to non-university males in the community, where 7.3.% disclose a history of such behaviors (Krahé et al, 2014). This supports prior contentions (e.g., Bloom et al, 2021) that universities are a breeding ground for sexual aggression and emphasizes the critical need for better harm prevention initiatives on campuses, including more evidence-based psychological interventions for male students who are at risk of offending.…”
Section: Discussionsupporting
confidence: 84%
“…No analogous research has been conducted in the UK; however, the prevalence of self-reported sexual aggression is notably higher amongst our participants compared to non-university males in the community, where 7.3.% disclose a history of such behaviours (Krahé et al, 2014). This supports prior contentions (e.g., Bloom et al, 2021) that universities are a breeding ground for sexual aggression and emphasizes the critical need for better harmprevention initiatives on campuses, including more evidence-based psychological interventions for male students who are at risk of offending.…”
Section: Discussionsupporting
confidence: 84%
“…This study identified this upstander position within the framework of the new alternative masculinities that has always taken a stand against gender-based violence by supporting the victims [29]. Gender violence is maintained in the context of university due to the relationships created by the structure of academia, where power hierarchies and abuse are present, besides the hostility against victims, the naturalization of violence and sexist stereotypes [26,30]. Suffering sexual harassment at university affects victims' productivity and educational performance because rejecting some teacher's proposals implies retaliation in qualifications [31].…”
Section: Introductionmentioning
confidence: 99%